2011
DOI: 10.1002/cncr.26598
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and therapeutic impact of the chromosome 20q13.2 ZNF217 locus amplification in ovarian clear cell carcinoma

Abstract: BACKGROUND:The goal of this study was to examine the clinical significance of ZNF217 amplification and assess whether ZNF217 could be a potential therapeutic target in ovarian clear cell carcinoma (OCCC). METHODS: ZNF217 expression and amplification in OCCC was assessed by immunohistochemistry, fluorescence in situ hybridization, and clinical data collected via a retrospective chart review. ZNF217 gene knockdown using silencing RNA (siRNA) was used to assess ZNF217 functions in OCCC cell lines. RESULTS: Gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 86 publications
4
56
2
1
Order By: Relevance
“…Absence of prognostic significance of PIK3CA mutations and PI3K-Akt pathway was confirmed in our study as in the previous studies. 10,27,35 In this study, we demonstrated that loss of PTEN expression was not an independent prognostic factor after multivariate analysis; this finding is similar to that of Ho et al 36 ZNF217 amplification was reported to be a poor prognostic factor in the study by Rahman et al, 32 while in this study, we did not find the prognostic effect of ZNF217 amplification. In brief, FIGO staging was the most important and the only prognostic factor in our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Absence of prognostic significance of PIK3CA mutations and PI3K-Akt pathway was confirmed in our study as in the previous studies. 10,27,35 In this study, we demonstrated that loss of PTEN expression was not an independent prognostic factor after multivariate analysis; this finding is similar to that of Ho et al 36 ZNF217 amplification was reported to be a poor prognostic factor in the study by Rahman et al, 32 while in this study, we did not find the prognostic effect of ZNF217 amplification. In brief, FIGO staging was the most important and the only prognostic factor in our study.…”
Section: Discussionsupporting
confidence: 89%
“…29,30 Recently, Krig et al 31 reported that ZNF217 could activate the PI3K-Akt pathway by regulating ErbB3 expression in breast cancer cells. ZNF217 amplification and PIK3CA mutations were almost mutually exclusive in the study by Rahman et al 32 In our study, the correlation between PIK3CA mutations and ZNF217 amplification was not statistically significant (data not shown, P ¼ 0.541). PIK3CA mutations and ZNF217 amplification affected 38 cases, and 6 cases (16%) harbored both PIK3CA mutations and ZNF217 amplification.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In previous studies, molecular alterations in ovarian clear cell carcinomas, including ARID1A, PIK3CA, and ZNF217, were either not considered a prognostic factor or signified different conclusions. 22,24,[32][33][34][35][36][37] Our study is the first report on the prognostic impact of TERT promoter mutations in early-stage ovarian clear cell carcinomas. TERT promoter mutations may have a role in the development of chemoresistance, but more in-depth investigations are necessary.…”
Section: Discussionmentioning
confidence: 68%
“…For example amplifications in the long arm of chromosome 20 have been associated with poor prognosis and chemotherapy resistance in breast and ovarian carcinoma [61, 62]. In head and neck squamous cell carcinoma 11q13 amplification is a marker of poor prognosis, whereas 3p and 11q loss is associated with resistance to chemotherapy and/or radiotherapy [63, 64].…”
Section: Cytogenetic Alterationsmentioning
confidence: 99%